Pengaruh Kualitas Pelayanan Terhadap Kepuasan Orang Tua Murid Di IEC, Medan - Ivan Irawan; Yuliana Yuliana; Arwin Arwin; Wilbert Jovando (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
The purpose of this study was to determine whether there is an effect of service quality on parental satisfaction at IEC, Medan. This research method is explanatory quantitative. Explanatory research or also called verification research aims to test a truth through testing hypotheses about causation between the various variables studied. The population in this study was 216 customers. The sampling technique in this study is the incidental sampling technique. The research sample is 68 customers by using Slovin formula. The result of the research is that there is an effect of service quality on the satisfaction of parents at IEC. Service quality is a form of consumer assessment of the level of service received or perceived as expected, so the quality of service is perceived as good and satisfactory. The research instrument used is the validity and reliability test. The data analysis technique used is simple linear regression. The correlation results are 0.601 and a significant value is 0.001 which indicates that the variables of service quality and customer satisfaction have a positive and strong relationship. From the results of r square of 47% and the remaining 53% is influenced by other factors. From the calculation of the regression analysis, the regression equation Y=8,250+0,126X is obtained. Thus it can be concluded that the quality of service affects the satisfaction of parents at IEC, Medan